Comparison of Prediction Programs for Short Wave Circuit Link from Iraq to Test points on Both Earth Hemispheres during Solar Minimum - Hasan, Ahmed Kadhim (Al-Khwarizmi Engineering Journal, 2021)
This paper compare the accurecy of HF propagation prediction programs for HF circuits links between Iraq and different points world wide during August 2018 when solar cycle 24 (start 2009 end 2020) is at minimun activity and also find out the best communication mode used. The prediction programs like Voice of America Coverage Analysis Program (VOACAP) and ITU Recommendation RS 533 (REC533 ) had been used to generat HF circuit link parameters like Maximum Usable Frequency ( MUF) and Frequency of Transsmision (FOT) .Depending on the predicted parameters (data) , real radio contacts had been done using a radio transceiver from Icom model IC 7100 with 100W RF power, tuner box and homemade dipole antenna of 10 m length and 8m height above ground. From correlation between the predicted data and observed data the result was not accurate .